Membangun Citra di Era Digital: Studi tentang Strategi Komunikasi Pemasaran Terpadu dalam Branding Produk UMKM Kafani Bandung - Eki Dwi Pratama; Rokibullah Rokibullah; Nappisah Nappisah (Riviera Publishing, 2025)
The advancement of digital technology has opened new opportunities for MSMEs to market their products more broadly, including ritual products such as burial shrouds, which were previously rarely promoted online. This phenomenon calls for a study on effective and contextual digital marketing strategies for building the brand image of religious products. This research aims to analyze the Integrated Marketing Communication (IMC) strategy implemented by the MSME Kafani in Bandung to promote burial shrouds through the TikTok platform. The study uses a qualitative case study with an exploratory approach, involving interviews, participant observation, social media content analysis, and documentation. The findings reveal that Kafani's marketing strategy combining educational, entertaining, and spiritual elements in a creative way successfully increases sales, expands market reach, and builds a strong, human-centered brand image. This study concludes that a digital-based edutainment approach can serve as an effective strategy for MSMEs to market religious products while maintaining cultural relevance and emotional connection with audiences.